The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/min7090161
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy and Processing of Hydrothermal Vein Quartz from Hengche, Hubei Province (China)

Abstract: Quartz occurs in many geological materials, and is used in numerous industrial fields as a raw material. Mineralogy and the processing of hydrothermal quartz were studied by optical microscope, electron probe microanalysis, scanning electron microscope, inductively coupled plasma-optical emission spectrometry, and inductively coupled plasma mass spectrometer. A combination of the geological occurrence of the quartz deposit, mineralogical studies, and the processing technologies of the hydrothermal quartz was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…However, the abundance and the variability of fluid inclusions suggest that this quartz benefitted from hydrothermal fluids inputs. Impurities contained in it are similar to some hydrothermal quartz data available [16,64]. Therefore, it is suggested that quartz in Etam was probably formed during metamorphic processes implying circulation of hydrothermal fluid saturated in silica [73], followed by silica precipitation and formation of hydrothermal veins.…”
Section: Geochemistry and Fluid Inclusionssupporting
confidence: 69%
See 2 more Smart Citations
“…However, the abundance and the variability of fluid inclusions suggest that this quartz benefitted from hydrothermal fluids inputs. Impurities contained in it are similar to some hydrothermal quartz data available [16,64]. Therefore, it is suggested that quartz in Etam was probably formed during metamorphic processes implying circulation of hydrothermal fluid saturated in silica [73], followed by silica precipitation and formation of hydrothermal veins.…”
Section: Geochemistry and Fluid Inclusionssupporting
confidence: 69%
“…Therefore, for quartz to be suitable as HPQ raw material, it should meet certain natural requirements, or the processing should be done by methods that are less hazardous and more efficient. Indeed, an efficient fluorine-free leaching system to purify quartz has been developed with an objective to establish a fluoride-free technology for improving quartz quality [16]. According to the authors, the method can consistently purify quartz by removing elements impurities up to 88.2 wt%, 99.0 wt% and 98.1 wt%, for the HCl-NH4Cl system, and 87.5 wt%, 98.1 wt% and 98.2 wt% for the H 2 SO 4 -NH 4 Cl system, respectively, for Al, K and Fe.…”
Section: Technological Aspectmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference between them is mainly in the content of impurities. Quartz may contain individual trace amounts of impurities including aluminum, iron, magnesium, calcium, titanium, potassium, lithium and boron, whereas quartzite contains quantifiable amounts of impurities which also form individual mineral-based compounds in the ore (e.g., calcite, hematite or dolomite) [1]. The main types of deposits for lump metallurgical quartz in geological terms are quartzite, hydrothermal quartz and pegmatite quartz (rock quartz) and fluvial quartz (gravel quartz) [2].…”
Section: Introductionmentioning
confidence: 99%
“…The papers by Götze et al [3], Lin et al [4], Pei et al [5] and Guatame-Garcia and Buxton [6] impressively demonstrate how advanced analytical methods are being used for the characterization of mineral properties and how this knowledge can be used for processing. The material that was investigated in these studies includes high-purity quartz from metamorphic host rocks, hydrothermal vein quartz, as well as diatomite.…”
mentioning
confidence: 99%